Severe hypoglycaemia requiring the assistance of emergency medical services--frequency, causes and symptoms - Krnacova, Veronika; Kubena, Ales; Macek, Karel; Bezdek, Martin; Smahelova, Alena; Vlcek, Jiri (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2012)
AIMS: To evaluate the incidence of severe hypoglycaemia (SH) requiring the assistance of Emergency Medical Services (EMS) in the general population of the Hradec Králové region, in a 1 year period; to describe the distribution of these events throughout the day, and to analyse the symptoms and causes. METHODS: The outcome data were obtained from special forms which were filled in by EMS medical staff. Incidence of SH was calculated and the distribution of events throughout the day was analysed using contingency tables. The relationship between blood glucose levels and the presence or absence of causes and symptoms of hypoglycaemia was evaluated using a general linear model and the regression tree technique. RESULTS: In all, a total of 338 events of SH were recorded in 262 patients. 150 episodes appeared in type 2 diabetic patients, 83 episodes in type 1 diabetic patients. 258 events were documented in insulin-treated patients. The incidence of SH was 2.4 and 0.4 episodes/100 patients/year for type 1 and type 2 diabetic patients, respectively. A significantly greater number of hypoglycaemic episodes was documented between 2 pm and 6 pm (P<0.001). Insulin therapy and alcohol consumption were the most dangerous causes of SH. CONCLUSIONS: Hypoglycaemia requiring the assistance of EMS represents an essential problem, especially in type 1 diabetic patients. The percentage of SH is comparable to other frequent diagnoses requiring the assistance of EMS in the region. This study reflects the behaviour of diabetic patients and highlights information which is important in the prevention of SH.
Keywords: urgentní zdravotnické služby; senioři; Hypoglycemia; Emergency Medical Services; Diabetes Mellitus, Type 1; mužské pohlaví; Diabetes Mellitus, Type 2; ženské pohlaví; Humans; hypoglykemie; Aged; Female; diabetes mellitus 2. typu; Male; lidé; diabetes mellitus 1. typu